Sulfur-Doped Carbon Nanotemplates for Sodium Metal Anodes - Yoon, Hyeon Ji; Hong, Seungki; Lee, Min Eui; Hwang, Junyeon; Jin, Hyoung-Joon; Yun, Young Soo (AMER CHEMICAL SOC, 2018)
Sodium metal is a good candidate as an anode for a large-scale energy storage device because of the abundance of sodium resources and its high theoretical capacity (similar to 1166 mA h g(-1)) in a low redox potential (-2.71 V versus the standard hydrogen electrode). In this study, we report effects of sulfur doping on highly efficient macroporous catalytic carbon nanotemplates (MC-CNTs) for a metal anode. MC-CNTs resulted in reversible and stable sodium metal deposition/stripping cycling over similar to 200 cycles, with average Coulombic efficiency (CE) of similar to 99.7%. After heat treatment with elemental sulfur, the sulfur-doped MC-CNTs (S-MC-CNTs) showed significantly improved cycling performances over 2400 cycles, with average CEs of similar to 99.8%. In addition, very small nucleation overpotentials from similar to 6 to similar to 14 mV were achieved at current densities from 0.5 to 8 mA cm(-2), indicating highly efficient catalytic effects for sodium metal nucleation and high rate performances of S-MC-CNTs. These results provide insight regarding a simple but feasible strategy based on bioabundant precursors and an easy process to design a high-performance metal anode.